Effectiveness of a Personalized, Chess-Based Training Serious Video Game in the Treatment of Adolescents and Young Adults With Attention-Deficit/Hyperactivity Disorder: Randomized Controlled Trial - María Rodrigo-Yanguas; Marina Martín-Moratinos; Carlos González-Tardón; Fernando Sanchez-Sanchez; Ana Royuela; Marcos Bella-Fernández; Hilario Blasco-Fontecilla (JMIR Publications, 2023)
BackgroundCompared with traditional approaches, gaming strategies are promising interventions for the treatment of attention-deficit/hyperactivity disorder (ADHD). We developed a serious game, The Secret Trail of Moon (TSTM), for ADHD treatment. ObjectiveThe main objective of this clinical trial was to demonstrate the effectiveness of an add-on, either TSTM or Therapeutic Chess (TC), in previously optimally drug-titrated, clinically stable patients with ADHD. MethodsThis study is a prospective, unicentric, randomized clinical trial in clinically stable patients with ADHD, aged 12 to 22 years. The TSTM (n=35) and TC groups (n=34) performed 12 weekly sessions of their respective treatments. The control group (CG) patients (n=35) were called by phone every week, but they received no cognitive intervention. The primary end point was the change from baseline to end point in the parent "Behavior Rating Inventory of Executive Function-2" (BRIEF-2; patients' parents) in the per-protocol population (31 serious videogame: 24 TC and 34 CG). ResultsOur study failed to probe clear-cut improvements in the global score of the BRIEF-2. However, the TC group showed improvements in measures of emotional control, emotional regulation, and inattention. The TSTM group showed improvements in measures of emotional regulation, inattention, and school context. ConclusionsTSTM and TC did not improve executive function symptoms, but they improved ADHD symptomatology related to emotional regulation. Further studies with bigger samples are required to confirm these preliminary findings. Trial RegistrationClinicalTrials.gov NCT04355065; https://clinicaltrials.gov/ct2/show/NCT04355065